Bio-Enlivened Behavioral Investigation of MANETs in Smart Cities - Tamilselvi, A; Ramaraj, E (International Journal of Computer Sciences and Engineering, 2018)
Internet of things (IoT), is a ground-breaking technology in this current world technology. It is the internet connectivity of physical sensible devices embedded with integrated actuators, circuit technology, software and radars that assist to gather and interchange data. IoT in smart cities interacts with mobile ad - hoc networks (MANET), is solitary compelling approaches to sort out a system as indicated by the system topological changes. MANET is similarly as wireless sensor networks (WSN). Collaboration between WSN and MANET with IoT, makes even more attractive to the operators and economically successful. MANET with the Io connected IoT allows the establishment of an innovative MANET-IoT system and sensor based networks. In this paper, the presented routing solution for MANET-IoT using ad-hoc network protocols and wireless network principles. The presented results of solution investigates a behavioural study of bird grouping that generates an effective methodology to well- organized energy and enhance the network lifetime in the MANET-IoT system. And it is a step forward to an unfailing facility of services over universal future internet infrastructure.